Educating Citizens for Active Democracy - Taiwo Isaac Olatunji; Vivek Kumar Chahar; Dare Rilwan Amusa; Adeyanju Adeonipekun; Ali Abdulrahman Saad (AS: Andragoška Spoznanja)
This study compared adult learning and education (ALE) programmes for promoting active democratic citizenship (ADC) in India and Nigeria by focusing on the aims of ALE, national education policies, and the main challenges confronting adult citizenship education. We adopted a theoretical framework which is an integration of multiple orientations of citizenship, including the liberal-democratic, communitarian, and republican traditions. The methodology comprised a document analysis of selected policies and reports. The findings highlight both the achievements and challenges faced by each country in fostering civic engagement. In India, ADC elements were embedded within broader socioeconomic development programmes, whereas in Nigeria, formal and non-formal education systems were pivotal in promoting ADC. However, both nations grappled with systemic barriers such as limited accessibility, policy instability, and sociocultural barriers. The study offers insights into the role of ALE programmes and government policies in fostering ADC in developing economies and multicultural nations.